2019
DOI: 10.1016/j.ejc.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Johnson’s bijections and their application to counting simultaneous core partitions

Abstract: Johnson recently proved Armstrong's conjecture which states that the average size of an (a, b)-core partition is (a+b+1)(a−1)(b−1)/24. He used various coordinate changes and one-to-one correspondences that are useful for counting problems about simultaneous core partitions. We give an expression for the number of (b 1 , b 2 , · · · , bn)-core partitions where {b 1 , b 2 , · · · , bn} contains at least one pair of relatively prime numbers. We also evaluate the largest size of a self-conjugate (s, s + 1, s + 2)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…We say a partition is the conjugate of λ, denoted by Hence we obtain the following corollary which was proved by Baek, Nam, and Yu [7].…”
Section: Remark 23mentioning
confidence: 72%
See 1 more Smart Citation
“…We say a partition is the conjugate of λ, denoted by Hence we obtain the following corollary which was proved by Baek, Nam, and Yu [7].…”
Section: Remark 23mentioning
confidence: 72%
“…As a consequence, we surprisingly find that the number of 2t-core partitions into l even parts equals the number of t-core partitions into l parts. In Section 3, inspired by a recent expression for simultaneous core partitions ( [7]), we give a new representation for simultaneous cores, which is useful in studying the topics on (s, s + 1, · · · , s + r)-cores. In the last section, we conclude this note with some formulas for the core partitions with distinct parts.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the number of (s, s + 1)-core partitions is the sth Catalan number C s = 1 s+1 2s s = 1 2s+1 2s+1 s . Going further, researchers considered simultaneous core partitions when the sequence of s i forms an arithmetic progression (see [1,4,6,16,17,18]). Recently, the authors [7] enumerated the (s, s + d, .…”
Section: Introductionmentioning
confidence: 99%
“…Since the work of Anderson, results on (s, t)-cores were published by many researchers (see [3,6,8,9,10,11]). Also, some researchers concerned with simultaneous core partitions whose cores line up in arithmetic progression (see [1,4,7,19,20,21]). Yang-Zhong-Zhou [21] showed that the number of (s, s + 1, s + 2)-core partitions is the sth Motzkin number M s = ⌊s/2⌋ k=0 s 2k C k , where C k is the kth Catalan number.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Baek-Nam-Yu [4] obtained an alternative proof for Theorem 1.3 and found a formula for the number of (s, s + d, s + 2d, s + 3d)-core partitions.…”
Section: Introductionmentioning
confidence: 99%